Statement by the Managing Director on the Independent Evaluation Office Report on IMF Engagement with Small Developing States : Executive Board Meeting May 6, 2022. (Policy Papers; Policy Paper ;, 2022)
The report and its recommendations should also be careful to not impinge upon areas that are still unfolding, such as the RST, crisis response, and CD provision, to avoid unnecessary duplication of efforts and ensure that a coherent and evenhanded framework is in place. I offer qualified and/or partial support to the recommendations, as discussed below, to serve better our SDS members.